2011
DOI: 10.15578/jra.6.3.2011.447-456
|View full text |Cite
|
Sign up to set email alerts
|

FREKUENSI PEMBERIAN PAKAN DAN TEKNOLOGI PRODUKSI IKAN BETUTU ( Oxyeleotris marmorata Blkr) DENGAN SISTEM TERKONTROL

Abstract: ABSTRAKSuatu percobaan untuk memperbaiki sintasan ikan betutu fase "Growth out" telah dilakukan di Laboratorium Basah Balai Riset Perikanan Budidaya Ar Tawar, Bogor. Wadah percobaan yang digunakan adalah fiber glass berdiameter 1,5 m dan ketinggian 0,5 m. Wadah dirancang sistem resirkulasi, melalui bak stok air (2,5 m 3 ) dan bak pemanasan air (0,6 m 3 ), kemudian pada masing-masing wadah pemeliharaan dirancang biofilter yang berfungsi membersihkan air. Air dari bak stok, dialirkan ke dalam bak pemanasan, kemu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
(12 reference statements)
0
3
0
1
Order By: Relevance
“…The temperature range in research showed that during rearing the temperature was still in a condition capable of supporting the life of Brazilian silver Arowana fish (Osteoglossum bicirrhosum), because of the use of a heater to keep the temperature in the aquarium within the appropriate range to support the life of silver Arowana fish Brazil. Water temperature has a major influence on fish survival because it indirectly affects metabolic work in the fish's body (Taufik et al, 2016).…”
Section: Water Qualitymentioning
confidence: 99%
“…The temperature range in research showed that during rearing the temperature was still in a condition capable of supporting the life of Brazilian silver Arowana fish (Osteoglossum bicirrhosum), because of the use of a heater to keep the temperature in the aquarium within the appropriate range to support the life of silver Arowana fish Brazil. Water temperature has a major influence on fish survival because it indirectly affects metabolic work in the fish's body (Taufik et al, 2016).…”
Section: Water Qualitymentioning
confidence: 99%
“…Berdasarkan hasil analisis jenis makanan yang terdapat dalam lambung ikan Betutu terdiri dari 5 kelompok, yaitu ikan, nematoda, debris hewan, serasah dan fitoplankton dapat dilihat pada Tabel 1. Menurut Azwar & Melati (2011), hasil pengamatan isi lambung ikan Betutu yang ditangkap dari alam berupa serangga, ikan, cacing, dan udang, akan tetapi pakan paling dominan ikanikan dan udang. Adanya serasah (potongan tumbuhan) yang ditemukan pada lambung ikan Betutu menunjukkan bahwa ikan tersebut mencari mangsa pada daerah litoral dan dalam mencari mangsa ikan Betutu merupakan predator demersal yang pasif (Riede, 2004).…”
Section: Jenis Makanan Ikan Betutuunclassified
“…In addition, the reason for this is that the temperature distribution in the waters of the Air Manna Estuarytends to be higher in value during low tide conditions. Because the temperature will be higher, above 26 degrees Celsius, this indicates that the supply of dissolved oxygen will be higher; consequently, this will have an effect on the ability of biota to survive in these waters [15]. Because the river water discharge that enters the estuary has a tendency to be fairly high, the Air Manna Estuarywas classified as belonging to the group of brackish water when the research was carried out.…”
Section: Temperaturementioning
confidence: 99%